Some Rulings on Ihram and Intention According to Imam al-Sharwani in His Marginal Commentary on Tuhfat al-Muhtaj (A Comparative Study) - Mahmoud Hassan Hussein, Hamed (Islamic Sciences Journal, 2025)
This study discusses the rulings of ihram and intention according to the views of Imam al-Sharwani as presented in his marginal notes on Tuḥfat al-Muḥtaj. It offers a comparative analysis of the juristic opinions across the major Islamic schools of thought regarding these issues. Chapter One outlines definitions of jurisprudence and its branches, as well as a biographical account of Imam Abd al-Ḥamid al-Sharwani, highlighting his upbringing, teachers, students, major works, and his death. Chapter Two focuses on specific issues concerning iḥram and intention, such as: The ruling on entering ihram for Hajj before the appointed months. Jurists differ: the majority deem it valid but disliked, while some Malikis and Shafiʿis consider it invalid. The ruling on a person performing a voluntary Hajj before completing the obligatory Hajj (Hijjat al-Islam). Opinions vary: the Hanafis and Malikis maintain that the intention is valid as made, whereas the Shafiʿis and Hanbalis argue that it defaults to the obligatory Hajj The research is based on presenting the juristic views with their evidences from the Glorious Qur’an, Sunnah, analogy, and reasoned argument, followed by a comparative evaluation and preference for the strongest view.